2009
DOI: 10.1086/644785
|View full text |Cite
|
Sign up to set email alerts
|

Low Bone Mineral Density, Renal Dysfunction, and Fracture Risk in HIV Infection: A Cross‐Sectional Study

Abstract: In this mostly male population, low BMD was significantly associated with PI therapy. Tenofovir recipients showed evidence of increased bone turnover. Measurement of BMD and estimation of fracture risk may be warranted in treated HIV-infected adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
4
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 30 publications
5
75
4
1
Order By: Relevance
“…Available data on the role for HIV-related factors in bone loss among HIV-1-infected patients are conflicting [6]. Some studies have suggested that the use of protease inhibitor and of TDF was associated with an increased risk of osteopenia and osteoporosis [1,12,17,24,25] while others failed to confirm this association [18,20,26,27]. In the present study, neither protease inhibitors nor TDF was associated to bone loss with statistical significance, although weak trends of association were observed at several sites for TDF.…”
Section: Discussioncontrasting
confidence: 71%
“…Available data on the role for HIV-related factors in bone loss among HIV-1-infected patients are conflicting [6]. Some studies have suggested that the use of protease inhibitor and of TDF was associated with an increased risk of osteopenia and osteoporosis [1,12,17,24,25] while others failed to confirm this association [18,20,26,27]. In the present study, neither protease inhibitors nor TDF was associated to bone loss with statistical significance, although weak trends of association were observed at several sites for TDF.…”
Section: Discussioncontrasting
confidence: 71%
“…Therefore, the power calculation of this study was computed using literature data on osteopenia in HIV+ve and HIV−ve patients [1,20,21]. Cases and controls were matched 1:2 by age (±3 years) and BMI (±0.5 kg/m 2 ).…”
Section: Statisticsmentioning
confidence: 99%
“…HIV-infected adults receiving ART have more osteopaenia than uninfected adults [61], and TDF has been associated with an increased risk of osteopenia compared with stavudine in randomized trials [62]. However, the fraction of risk attributable to cART regimen components, HIV infection and patient characteristics is still unclear [63], and no recommendations have yet been issued regarding bone mineral density screening for TDF use.…”
Section: Overview Of Alternative First-line Optionsmentioning
confidence: 99%